2008
DOI: 10.2147/ndt.s1026
|View full text |Cite
|
Sign up to set email alerts
|

Management of epilepsy in the elderly

Abstract: Epilepsy among the elderly is a frequently occurring pathology, differing in etiology, clinical presentation and prognosis from those of young people. In addition, beyond a certain age, physiological modifi cations are produced in the metabolism which alter the pharmacokinetics of antiepileptic drugs (AEDs), increasing the risk of pharmacological interactions, already greater in these patients due to the frequency of poly-pharmacy. Furthermore, elderly patients are particularly sensitive to certain secondary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Given that studies have found few differences in the ability of the ASMs to control seizures, selection is largely driven by the other factors. Adverse side effects from ASMs negatively impact QoL in older adults and can lead to noncompliance 27 . Studies involving younger adults have shown most ASMs can affect memory, cognition, mood, somnolence, and other issues.…”
Section: Treatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that studies have found few differences in the ability of the ASMs to control seizures, selection is largely driven by the other factors. Adverse side effects from ASMs negatively impact QoL in older adults and can lead to noncompliance 27 . Studies involving younger adults have shown most ASMs can affect memory, cognition, mood, somnolence, and other issues.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Adverse side effects from ASMs negatively impact QoL in older adults and can lead to noncompliance. 27 Studies involving younger adults have shown most ASMs can affect memory, cognition, mood, somnolence, and other issues. Older adults would likely experience these ASM-specific effects, but the degree may be different and more severe.…”
Section: Practical Considerations In Drug Selectionmentioning
confidence: 99%
“…The treatment of elderly patients with epilepsy is particularly challenging, as this age group is rarely represented in the clinical trials that have led to the approval of the different antiseizure medications (ASMs) [1,8]. Treatment is complicated by the presence of physiological changes related to aging, comorbidities, cognitive problems, and concerns regarding drug interactions and medication adherence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these patients have a higher incidence of comorbidities and a higher use of concomitant medications that may result in drug-drug interactions [1,2,[9][10][11], including not only interactions with other drugs but also interactions between different ASMs in a polytherapy regimen [6]. Furthermore, age-related physiological changes such as hepatic and renal impairment affect the pharmacokinetics and pharmacodynamics of ASMs and may affect the nature, incidence, and severity of adverse events (AEs) [3,6,11], making these patients particularly sensitive to certain secondary effects of ASMs, such as, for example, cognitive disturbances, hyponatremia, or osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologically, epilepsy affects around 70 million people worldwide [2] and has a substantial effect not only on the health/wellbeing of people but also on the economic productivity and burden on health care services [3]. Currently, epilepsy is managed by using many antiepileptic drugs, such as phenytoin, carbamazepine, and phenobarbitone [4]. However, using these drugs is associated with severe side effects that may limit its utilization in epilepsy management [5].…”
Section: Introductionmentioning
confidence: 99%